Clinical- and cost-effectiveness of the STAR care pathway compared to usual care for patients with chronic pain after total knee replacement: study protocol for a UK randomised controlled trial - Wylde, V; Bertram, W; Beswick, A; Blom, A; Bruce, J; Burston, A; Dennis, J; Garfield, K; Howells, N; Lane, A; McCabe, C; Moore, A; et al. (BioMed Central, 2018)
Background Approximately 20% of patients experience chronic pain after total knee replacement. There is little evidence for effective interventions for the management of this pain, and current healthcare provision is patchy and inconsistent. Given the complexity of this condition, multimodal and individualised interventions matched to pain characteristics are needed. We have undertaken a comprehensive programme of work to develop a care pathway for patients with chronic pain after total knee replacement. This protocol describes the design of a randomised controlled trial to evaluate the clinical- and cost-effectiveness of a complex intervention care pathway compared with usual care. Methods This is a pragmatic two-armed, open, multi-centred randomised controlled trial conducted within secondary care in the UK. Patients will be screened at 2 months after total knee replacement and 381 patients with chronic pain at 3 months postoperatively will be recruited. Recruitment processes will be optimised through qualitative research during a 6-month internal pilot phase. Patients are randomised using a 2:1 intervention:control allocation ratio. All participants receive usual care as provided by their hospital. The intervention comprises an assessment clinic appointment at 3 months postoperatively with an Extended Scope Practitioner and up to six telephone follow-up calls over 12 months. In the assessment clinic, a standardised protocol is followed to identify potential underlying causes for the chronic pain and enable appropriate onward referrals to existing services for targeted and individualised treatment. Outcomes are assessed by questionnaires at 6 and 12 months after randomisation. The co-primary outcomes are pain severity and pain interference assessed using the Brief Pain Inventory at 12 months after randomisation. Secondary outcomes relate to resource use, function, neuropathic pain, mental well-being, use of pain medications, satisfaction with pain relief, pain frequency, capability, health-related quality of life and bodily pain. After trial completion, up to 30 patients in the intervention group will be interviewed about their experiences of the care pathway. Discussion If shown to be clinically and cost-effective, this care pathway intervention could improve the management of chronic pain after total knee replacement.